ECPGR challenges in rye germplasm conservation: Proceedings of an International Conference on Crop Germplasm Conservation with Special Emphasis on Rye, and an ECP/GR Workshop, 2-6 July 1996, Warsaw/Kostancin-Jeziorna, Poland - Gass, T.; Podyma, W.; Puchalski, J.; Eberhart, S.A.; European Cooperative Programme for Plant Genetic Resources (1998)
The first and major part of this publication, devoted to the proceedings of the conference on crop germplasm conservation with special emphasis of rye, consists of 22 papers grouped into five sessions: (1) plant genetic resources conservation and rye breeding in Poland; (2) long-term storage practices for orthodox seeds; (3) long-term storage and seed deterioration; (4) diversity analysis and rye germplasm evaluation; and (5) rye germplasm collections in Europe. The second part of this publication reports discussions from the ECP/GR Secale Genetic Resources workshop, which considers the European Secale Database and the European Secale collection. An appendix listing participants is included. (Abstract © CAB ABSTRACTS, CAB International)